2023
DOI: 10.1093/plphys/kiad403
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar sugar transporter EARLY RESPONSE TO DEHYDRATION6-LIKE4 affects fructose signaling and plant growth

Abstract: Regulation of intracellular sugar homeostasis is maintained by regulation of activities of sugar import and export proteins residing at the tonoplast. We show here that the EARLY RESPONSE TO DEHYDRATION6-LIKE4 (ERDL4) protein, a member of the monosaccharide transporter family, resides in the vacuolar membrane in Arabidopsis (Arabidopsis thaliana). Gene expression and subcellular fractionation studies indicated that ERDL4 participates in fructose allocation across the tonoplast. Overexpression of ERDL4 increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…It has been proposed for a long time that an excess sugars can trigger negative feedback regulation of leaf photosynthesis (Paul and Foyer 2001; Ainsworth and Bush 2011). In agreement with this, the disruption or overexpression of genes coding for sugar transporters, which potentially impact the cytosolic sugar availability, induce modifications of the photosynthetic performance (Wingenter et al 2010; Frost et al 2012; Khan et al 2023; Liu et al 2023b; Valifard et al 2023). In an effort to gain more knowledge on the physiological consequences of impaired SWEET-mediated sugar transport, we measured chlorophyll fluorescence on the swt11swt12 , swt16swt17 and swt-q mutant lines along with the Col-0 wild-type (WT) plants.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been proposed for a long time that an excess sugars can trigger negative feedback regulation of leaf photosynthesis (Paul and Foyer 2001; Ainsworth and Bush 2011). In agreement with this, the disruption or overexpression of genes coding for sugar transporters, which potentially impact the cytosolic sugar availability, induce modifications of the photosynthetic performance (Wingenter et al 2010; Frost et al 2012; Khan et al 2023; Liu et al 2023b; Valifard et al 2023). In an effort to gain more knowledge on the physiological consequences of impaired SWEET-mediated sugar transport, we measured chlorophyll fluorescence on the swt11swt12 , swt16swt17 and swt-q mutant lines along with the Col-0 wild-type (WT) plants.…”
Section: Resultsmentioning
confidence: 92%
“…Briefly, the raw data were transformed using squareroot and a differential expression analysis was performed using the lmfit model of the limma package (Ritchie et al 2015). The Rflomics package was also used to re-analyze the RNA-seq results obtained in Khan et al (2023). Filtering and normalization strategies were performed as described in Lambert et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, transcripts of proteins involved in vacuolar export such as the H + /sucrose symporter MeSUT4b (Schneider et al, 2012), as well as all three EARLY RESPONSE TO DEHYDRATION 6 ( MeERD6 ) proteins (Kiyosue et al, 1998), and two out of three MeEDL4/ERDL6 orthologs (Poschet et al, 2011) decreased throughout bulking (cluster SR 2 or 3). ERD6 and ERD6-like proteins are part of the MST family and facilitate H + /hexose symport across the tonoplast (Pommerrenig et al, 2018, Khan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The MST gene family includes a plethora of genes encoding for proteins involved in tonoplast or plastid transport (Pommerrenig et al, 2018). While transcripts of proteins involved in vacuolar/plastidic import generally increased when cytosolic sugar levels are high, those involved in vacuolar/plastidic export generally decreased in expression under latter conditions (Wormit et al, 2006, Patzke et al, 2018, Klemens et al, 2013, Khan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Khan et al (2023) reported the positive role of ERDL4 ( EARLY RESPONSE TO DEHYDRATION 6-LIKE4 ) in promoting growth and cold tolerance in Arabidopsis. ERDL4 encodes a fructose transporter located at the vacuolar membrane.…”
mentioning
confidence: 99%